Leukemic Ischemia: A Case of Myocardial Infarction Secondary to Leukemic Cardiac Involvement. (7th August 2017) - Fursevich, Dzmitry; Zuchowski, Colin; Limback, Joseph; Kendall, Melissa; Ramirez, Ashley; Fanaian, Naim; Burt, Jeremy
Abstract : We report a case of a 39-year-old male who presented to the emergency department with acute chest pain while being in remission from T-cell acute lymphoblastic leukemia (T-ALL). Cardiac markers were elevated and EKG revealed ischemic changes compatible with acute myocardial ischemia. Coronary computed tomography angiography (CCTA) showed calcium-free coronary arteries and soft tissue myocardial infiltration suggestive of cardiac leukemia. A bone marrow biopsy confirmed recurrence of T-ALL, and patient was successfully treated with chemotherapy. We discuss the prospective diagnosis of myopericardial leukemic involvement and the role of CCTA in diagnosis and perform a literature review.